Low-loss superconducting aluminum microwave coplanar waveguide resonators on sapphires for the qubit readouts. (1st June 2022) - He, Q; OuYang, P; Gao, H; He, S; Li, Y; Wang, Y; Chen, Y; Dai, X; Wang, Y; Wei, L F
Abstract: The coplanar waveguide (CPW) microwave resonators have been widely applied for solid-state quantum computation and single-photon detection. Based on the physical analysis for the high fidelity readouts of the qubit(s), in this paper we design and then fabricate accordingly the desired aluminum (Al) film quarter-wavelength resonators on sapphire substrates. The ultra-low temperature measurement results show that the linearity of the internal quality factor under the proper driving power is satisfied well for the high fidelity readouts of the qubit(s); and the phase- and amplitude fractional frequency noises are significantly less for avoiding the potential information false alarms of the detected qubit during the readouts. With the demonstrated qubit-resonator experimental parameters, we argue that the designed and fabricated quarter-wavelength CPW resonators, with optimized parameters, can be used to implement the desired weakly perturbing readout measurements of the solid-state qubits on-chip.